1996
DOI: 10.1021/ic9516166
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Substitution Reactions of Sulfur(VI)−Nitrogen−Phosphorus Rings:  Reactions of the Halogenated Cyclic Thionylphosphazenes [NSOX(NPCl2)2] (X = Cl or F) with Oxygen-Based Nucleophiles

Abstract: The reactions of the cyclic thionylphosphazenes [NSOX(NPCl(2))(2)] (1, X = Cl; 2, X = F) with three oxygen-based nucleophiles of increasing basicity, sodium phenoxide (NaOPh), sodium trifluoroethoxide (NaOCH(2)CF(3)), and sodium butoxide (NaOBu) have been studied. The reaction of 1 and 2 with 4 equiv of NaOPh at 25 degrees C yielded the regioselectively tetrasubstituted species [NSOX{NP(OPh)(2)}(2)] (5d, X = Cl; 6d, X = F). Further reaction of 5d with an additional 2 equiv of NaOPh over several days or at elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Care was taken to exclude water from all the reactions described here, and it can be assumed that the attacking species is trifluoroethoxide rather than hydroxide. A similar cleavage mechanism and products have also been detected from the reaction of excess nucleophile with heterophosphazenes by Manners et al 40 Nevertheless, a key reaction to supplement the side group exchange studies is the interaction of hexakis(2,2,2trifluoroethoxy)cyclophosphazene ( 1) with sodium trifluoroethoxide (molar ratio 1 : 12) under the same reaction condition as in all the other reactions. As shown in Fig.…”
Section: Stability Of 1 2 6 and 7 In The Presence Of Nucleophilessupporting
confidence: 59%
“…Care was taken to exclude water from all the reactions described here, and it can be assumed that the attacking species is trifluoroethoxide rather than hydroxide. A similar cleavage mechanism and products have also been detected from the reaction of excess nucleophile with heterophosphazenes by Manners et al 40 Nevertheless, a key reaction to supplement the side group exchange studies is the interaction of hexakis(2,2,2trifluoroethoxy)cyclophosphazene ( 1) with sodium trifluoroethoxide (molar ratio 1 : 12) under the same reaction condition as in all the other reactions. As shown in Fig.…”
Section: Stability Of 1 2 6 and 7 In The Presence Of Nucleophilessupporting
confidence: 59%
“…The unexpected regioselectivity of substitution of the poly(thionylphosphazenes) with aryloxide nucleophiles and the rapid degradation of the polymer backbone with alkoxide nucleophiles prompted us to model this behaviour by studying the reactions of the cyclic thionylphosphazenes 16 and 18 towards representative aryloxide and alkoxide reagents. 56 The substitution reactions with NaOPh were found to conform to the following general order of reactivity, PCl 2 > PCl(OPh) > S(O)X (X = Cl or F). As in the case of the polymer, the substitution of the S᎐Cl bonds did not take place under normal reaction conditions, but it was found that upon the addition of an excess of NaOPh and reaction for several days at 25 ЊC or reflux for 4 h, the fully substituted cyclic thionylphosphazene could be formed.…”
Section: Synthesis and Properties Of Moisture-stable Poly-(thionylpho...mentioning
confidence: 89%
“…The reactions of cyclic model compounds with nucleophiles have been invaluable in the elucidation of the substitution pathways for polyphosphazenes . We have recently reported that when cyclic thionylphosphazenes, 1a and 1b , are treated with sodium alkoxides or aryloxides, substitution proceeds regioselectively, initially at phosphorus and subsequently at sulfur , Our model studies suggest that the synthesis of alkoxy-substituted poly(thionylphosphazenes) should be possible, and this paper reports the first examples of poly(thionylphosphazenes) with high loadings of trifluoroethoxide (tfe).…”
Section: Resultsmentioning
confidence: 91%
“…Attempts to produce a polymer with 100% loading of trifluoroethoxide via the reaction of 2a with 5 equiv of Na[OCH 2 CF 3 ] led to backbone cleavage, and the product detected by 31 P NMR was the six-membered ring [NSO(OCH 2 CF 3 ){NP(OCH 2 CF 3 ) 2 } 2 ] (see ref ).…”
Section: Referencesmentioning
confidence: 99%